2020
DOI: 10.3389/fpsyg.2020.01078
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effects of Language-Switching Frequency on Attentional and Executive Functioning in Proficient Bilinguals

Abstract: Recent studies have proposed that the executive advantages associated with bilingualism may stem from language-switching frequency rather than from bilingualism per se (see, for example, Prior and Gollan, 2011). Barbu et al. (2018) showed that highfrequency switchers (HFLSs) outperformed low-frequency switchers (LFLSs) on a mental flexibility task but not on alertness or response inhibition tasks. The aim of the present study was to replicate these results as well as to compare proficient (HFLSs and LFLSs) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Thus, children learning English as L2 could more quickly show a higher rate of switching behaviors between L1 and L2, as a certain level of L2 and a number of exposition opportunities are required to lead to switching behaviors. This switching behavior has been related to better cognitive flexibility abilities in bilingual adult studies (e.g., Barbu et al, 2018;Barbu et al, 2020). These authors compared two groups of highly proficient bilinguals and found an advantage in the cognitive flexibility task in favor of the group that presented a high (vs. low) rate of switching behaviors in daily life.…”
Section: The Linguistic Characteristics Of the Languages At Stakementioning
confidence: 96%
“…Thus, children learning English as L2 could more quickly show a higher rate of switching behaviors between L1 and L2, as a certain level of L2 and a number of exposition opportunities are required to lead to switching behaviors. This switching behavior has been related to better cognitive flexibility abilities in bilingual adult studies (e.g., Barbu et al, 2018;Barbu et al, 2020). These authors compared two groups of highly proficient bilinguals and found an advantage in the cognitive flexibility task in favor of the group that presented a high (vs. low) rate of switching behaviors in daily life.…”
Section: The Linguistic Characteristics Of the Languages At Stakementioning
confidence: 96%
“…The balance in language use has been widely discussed as a core factor to explain the bilingual advantage (Verreyt et al, 2016;Yang et al, 2016;Hartanto and Yang, 2020). Even in balanced bilinguals, only high-frequency language switchers showed an advantage over monolinguals in tasks that measure cognitive flexibility (Barbu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This could also increase the switching opportunities of the child between his two languages. Moreover, this switching behaviour has been linked with the advantage found in cognitive flexibility tasks [ 15 , 16 ]. The children learning English as L2 could thus present the bilingual cognitive advantages earlier in their schooling.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas Barbu, Gonzalez, Gillet, & Poncelet [ 29 ] showed that French-speaking children immersed in English since two years did not present an advantage on executive functions nor on addition calculations, they showed, surprisingly, a disadvantage for immersed children in subtraction calculations. According to these authors, as the immersed children do not master their L2 sufficiently, they use important attentional resources when processing L2 information given by teachers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation